2020
DOI: 10.7759/cureus.7039
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Miniplate and K-wire in the Treatment of Metacarpal and Phalangeal Fractures

Abstract: Introduction Metacarpal and phalangeal fractures are common upper limb fractures due to direct blows, axial loading, and torsional loading injuries. The universal goal in treating all fractures for the patient to achieve normal motion, but the ideal technique for stabilization is still debated. For internal fixation, Kirschner wires (K-wires) or miniplates can be used, and each carries certain advantages. No previous study has compared K-wire use to miniplate use in treating metacarpal and phalangeal fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…A study conducted by Ahmad et al 17 reported that patients received mini-plates had shorter time of union of bone as compared to those who received K-wire fixation (11.80±2.38 Vs 12.95±3.38).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Ahmad et al 17 reported that patients received mini-plates had shorter time of union of bone as compared to those who received K-wire fixation (11.80±2.38 Vs 12.95±3.38).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, the patients in the study by Egloff et al were around 35 years old [ 10 ]. Pandey et al report an average of 29 years in their Italian study [ 11 ], and Ahmed et al have an average age in Pakistan of around 25 years [ 12 ]. An exception is the epidemiological study by Voth et al on hand injuries in children [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 85% of the fractures, consolidation was confirmed radiologically as well as clinically (119/140). In the literature, consolidation has been reported from 87% to 97% [ 12 ], [ 11 ], [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hand fractures are debilitating injury, and when multiple metacarpal shaft fractures occur, they can result in significant functional impairment. Multiple metacarpal shaft fractures of the hand significantly influence the individual's ability to perform routine activities [1][2][3] . Metacarpal fractures constitute 10% of total fractures in body and account for 36% of total hand fractures.…”
Section: Introductionmentioning
confidence: 99%